2001
DOI: 10.1002/ijc.1486
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the human major vault protein in astrocytic brain tumor cells

Abstract: Evidence has shown that the major human vault protein (MVP), which is identical to lung resistance-related protein (LRP), may be causally involved in a special type of multidrug resistance (MDR). The purpose of this study was to investigate the expression and cellular localization of MVP in cells derived from brain tumors and other tumors of neuroectodermal origin. Using both established cell lines (n ‫؍‬ 22) and primary explants (n ‫؍‬ 30), we show that a distinct overexpression of the MVP gene at the mRNA (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 20 publications
9
53
2
Order By: Relevance
“…In our cell model, we found very low levels of mdr1 mRNA without detectable P-gp, persistent expression of MRP1, and reduction of MVP expression especially in BTL3 cells. In a previous study, we observed correlation between MVP expression of glioblastoma cells and resistance to anthracyclines (Berger et al, 2001), which suggests a contribution of MVP at least to doxorubicin hypersensitivity of BTL3 cells. Additionally, EGFR-transmitted signals are known to contribute to apoptosis resistance of glioblastoma cells (Shinojima et al, 2003) leading, for example, to CDDP insensitivity (Nagane et al, 1998).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In our cell model, we found very low levels of mdr1 mRNA without detectable P-gp, persistent expression of MRP1, and reduction of MVP expression especially in BTL3 cells. In a previous study, we observed correlation between MVP expression of glioblastoma cells and resistance to anthracyclines (Berger et al, 2001), which suggests a contribution of MVP at least to doxorubicin hypersensitivity of BTL3 cells. Additionally, EGFR-transmitted signals are known to contribute to apoptosis resistance of glioblastoma cells (Shinojima et al, 2003) leading, for example, to CDDP insensitivity (Nagane et al, 1998).…”
Section: Discussionmentioning
confidence: 64%
“…When comparing alkylating agents with several other chemotherapeutics, an increased response in the recurrence-derived BTL cell lines was also observed in anthracyclines, whereas all cells were persistently unresponsive to VP-16, CDDP, and bleomycin. Highintrinsic chemoresistance of glioma cells has been reported by us and other groups involving overexpression of known drugresistance proteins like P-gp, MRP1, and MVP (Berger et al, 2001;Bredel, 2001;Spiegl-Kreinecker et al, 2002). In our cell model, we found very low levels of mdr1 mRNA without detectable P-gp, persistent expression of MRP1, and reduction of MVP expression especially in BTL3 cells.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Primary cell cultures were established from 48 histopathologically-confirmed human melanomas (10), three glioblastomas (11), and four soft tissue sarcomas. The SK-Mel-28, Calu-6, and HepG2 cell lines were obtained from the American Type Culture Collection (Rockville, MD), and the F2000 embryonic fibroblasts were obtained from Flow, Scotland.…”
Section: Materials and Methods Cell Culturesmentioning
confidence: 99%